FORMULATION OF AEROSOL CONCENTRATES CONTAINING HARUAN (Channa striatus) FOR WOUND DRESSING - FEBRIYENTI; AZMIN MOHD. NOOR; SARINGAT BAIE (Universiti Sains Malaysia, 2008)
The objective of this research was to formulate an aerosol concentrate containing haruan (Channa striatus) water extract that would produce a thin film when sprayed onto a wound and could be used for wound dressing. The aerosol concentrates were formulated with various polymer and plasticiser mixtures and tested in dispersion systems. The polymers evaluated were hydroxypropyl methylcellulose (HPMC), carboxymethylcellulose sodium (CMC Sodium), acacia, tragacanth, chitosan, gelatine and gelatine (bloom 151-160), all at concentrations of 2%. The plasticisers evaluated were polyethylene glycol (PEG) 400 and 4000, glycerine, propylene glycol, and triacetin. Films were prepared from film-forming dispersions by casting techniques. Film-forming dispersions were characterised in terms of pH, density, surface tension, rheological properties, particle size distribution, and tackiness. Based on these evaluations, HPMC was chosen as the best polymer. It produced a film with the expected qualities and was easy to reproduce in the form of dispersions or as thin transparent films. Glycerine was judged as the most appropriate plasticiser because it produced the concentrate having the desired qualities and properties expected from an aerosol concentrate